2016
DOI: 10.1371/journal.pone.0161282
|View full text |Cite
|
Sign up to set email alerts
|

Possible Contribution of Zerumbone-Induced Proteo-Stress to Its Anti-Inflammatory Functions via the Activation of Heat Shock Factor 1

Abstract: Zerumbone is a sesquiterpene present in Zinger zerumbet. Many studies have demonstrated its marked anti-inflammatory and anti-carcinogenesis activities. Recently, we showed that zerumbone binds to numerous proteins with scant selectivity and induces the expression of heat shock proteins (HSPs) in hepatocytes. To dampen proteo-toxic stress, organisms have a stress-responsive molecular machinery, known as heat shock response. Heat shock factor 1 (HSF1) plays a key role in this protein quality control system by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…In addition, previous work by Igarashi et al [47] showed that zerumbone (which its structure related to radicicol and geldanamycin) in Zingiber zerumbet Smith, increased cellular protein aggregates and promoted nuclear translocation of heat shock factor 1 (HSF1), which down-regulation attenuated the suppressive effects of zerumbone on mRNA and protein expressions of pro-inflammatory genes, including inducible nitric oxide synthase and IL-1β. In this study, geldanamycin isolated from Streptomyces zerumbet; an endophyte of Zingiber zerumbet, has structure related to zerumbone from Zingiber zerumbet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous work by Igarashi et al [47] showed that zerumbone (which its structure related to radicicol and geldanamycin) in Zingiber zerumbet Smith, increased cellular protein aggregates and promoted nuclear translocation of heat shock factor 1 (HSF1), which down-regulation attenuated the suppressive effects of zerumbone on mRNA and protein expressions of pro-inflammatory genes, including inducible nitric oxide synthase and IL-1β. In this study, geldanamycin isolated from Streptomyces zerumbet; an endophyte of Zingiber zerumbet, has structure related to zerumbone from Zingiber zerumbet.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that zerumbone, a sesquiterpene present in Zingiber zerumbet Smith, induced proteo-stress and HSR for promoting HSF1 activation in hepatoma cells, which were associated with its anti-inflammatory effects. (9)(10)(11) Similarly, other recent findings indicate that the physiological functions of curcumin are partially mediated by regulation of PQC systems, (12)(13)(14)(15) and it is known to induce HSR in human leukemia cells by activating HSF1. (12) As the most abundant and essential energy carrier in cells, ATP functions to drive a variety of biochemical reactions.…”
mentioning
confidence: 79%
“…Interestingly, we recently found that proteo-stress induced by zerumbone plays an important role in its antiinflammatory functions through HSF1 activation. (11) In addition to target molecule-mediated mechanisms, xenobiotic stress-mediated mechanisms may also be described as an intrinsic property to phytochemicals, which are secondary metabolites and have no nutritional value to animals. In fact, curcumin exhibits quite a low level of bioavailability and rapid excretion from the body, (49) common characteristics of phytochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, treatment of RAW264.7 macrophage with zerumbone led to marked nuclear translocation of HSF1 for HSP70 protein expression. ( 90 ) Interestingly, pretreatment with N -acetyl- l -cysteine (competitive nucleophile that reacts with zerumbone) or 4-phenylbutyric acid (chemical chaperone ( 91 ) ) reduced the suppressive effects of zerumbone on LPS-induced inducible nitric oxide synthase and COX-2 expression. Similarly, the suppressive effects of zerumbone on LPS-induced pro-inflammatory gene expressions were significantly diminished in HSF1-downregulated cells.…”
Section: Unique Role Of Proteo-stress In Anti-inflammatory Functionsmentioning
confidence: 99%